"Opening up a well of emotions": A qualitative study of men's emotional experiences in the transition to fatherhood. Issue 4 (20th November 2022) - Solberg, Beate; Glavin, Kari; Berg, Rigmor C.; Olsvold, Nina
Abstract: Aim: To explore the emotional changes and reactions men experience in their transition to fatherhood. Design: This study used a qualitative design. Methods: Data were collected through in‐depth interviews with 13 Norwegian fathers. Results: Through thematic analysis, three main themes were developed: (1) from self‐focus to family perspective; (2) emotional vulnerability; and (3) from insecurity to self‐assurance. The themes describe fathers' emotional process during the child's first year of life, ranging from positive feelings like affection and mastery, to challenging feelings like exclusion, jealousy and exhaustion. Many fathers describe taboos and shame over their own emotional reactions, although these can be considered a natural part of the postnatal period.